University aspirational pathways for metropolitan and regional students: Implications for supporting school-university outreach partnerships. - Vernon, Lynette; Watson, S.; Taggart, A. (SPERA, 2017)
Young people in low socioeconomic (SES) regions, including regional and rural areas of Australia, aspire to attend university after high school at a comparable rate to young people in higher SES regions. However, without concrete opportunities to support and develop their aspirations, students in regional areas are unable to internalize the goals of a university education. Therefore, university participation rates are lower for regional than metropolitan students. This study examines the roles of aspiration and expectation to attend university for regional and metropolitan high school students living in a low-SES region of Western Australia, where a four-year university aspiration project was implemented. Specifically, the directionality of the development of university desire and expectation is tested using data collected over 18 months within a cross-lagged modeling framework. Differences within the region are explored using multiple group analysis, comparing the model of a regional sample with the model of propensity-score matched metropolitan sample. The results demonstrate that for metropolitan students within the region, higher early university desire feeds higher university expectations, which, in turn, crystalise subsequent university desires. For regional students, however, the cross-lagged effects were not demonstrated, suggesting other neighbourhood factors, beyond familiarity with university pathways, remain for when low-SES students live further from a major city. These findings suggest that within the same low-SES region, there is variation in how the culture and neighborhood factors interact to determine the efficacy of university participation widening programs. Addressing logistic factors that restrict access to university may further reduce the participation gap.